A profile of food service operations in selected manufacturing plants in Mandaluyong, Rizal - Feliciano, Lina Rosario Dabu
This is a survey of food service operations in 41 manufacturing plants in Mandaluyong, Rizal. These plants belonged to 34 corporations which were among the top 1000 corporations in the country in 1973 in terms of sales. Data were obtained by interview from the general manager or his authorized representative and the person incharge of the food service operation. General Characteristics of the Manufacturing Plants and the Food Service All of the manufacturing plants were owned by corporations. Ownership by nationality was 21 Filipino-owned, 11 shared Filipino-foreign ownership, and nine foreign-owned. There were a total of 15, 300 employees in the 41 plants during the month of February 1975. Of the 41 plants, 33 provided food service to their employees out of whom 13 gave some form of meal subsidy. Twenty-six food service units serviced the 33 manufacturing plants that provided food service. Twenty-three were operated by concessionaires, two by the manufacturing plant management, and one by an employees' club. All food service units operated by concessionaires were covered by contracts, which varied by the length of the contractual period and space, equipment, and utilities provided by management. The meals served by the food service units were breakfast, lunch and supper meals, as well as morning and afternoon snack. The number of meals depended on the number of employees and the number of days of operation of the manufacturing plants. The concessionaire-operated food service units had an a la carte menu and the two plant-operated food service units had table d'hote. The concessionaire-operated food service units had more extensive menu patterns than those of the plan-operated food service units. The meal prices of the two plant-operated food service units, which had substantial meal subsidies were very minimal when compared with those of the concessionaire-operated food service units. In the operation of the food service unit, the problems encountered were related to purchasing, menu planning, and replacement of losses of small equipment. The Person Incharge of Food Service The persons incharge of the two plant-operated food service units had the job titles of Food Service Manager and Food Service Supervisor. The job title Concessionaire was used for the person incharge of food service units under contract with the plant management. Characteristics of Employment in the Food Service Units Job titles used for supervisory positions were food Service Manager, Food Service Supervisor, Food Production Supervisor and Concessionaire. In the non-supervisory positions, the job titles used were Cashier, Cook, Assistant Cook, Food Service Helper, Counter Attendant, Busboys, Dishwasher, and Utility Man/Woman. Majority of the employees in the food service units were females. The mean starting salaries of comparable positions in plant-operated food service units were 3.5 to 7.1 times higher than those in the concessionaire-operated food service units. Many concessionaire-operated food service units did not pay the minimum wage to their employees. There were fringe benefits given to food service employees in plant-operated than in concessionaire-operated food service units. Employee turnover in the food service units ranged from 5.7 to 50.0 percent. Majority of the food service units provided training to their employees. The kind of training given was predominantly informal. The findings in the study point out the need for setting up educational programs for concessionaires of food service units in manufacturing plants, the need for developing training programs for food service workers, the need to upgrade wages and salaries, and fringe benefits in concessionaire-operated food service units, and the need to set up minimum requirements on the qualifications of food service operators.